ANGELA MILLION, CHRISTIAN HAID, IGNACIO CASTILLO ULLOA, NINA BAUR - Spatial Transformations. Kaleidoscopic Perspectives on the Refiguration of Spaces - Borrego Gómez-Pallete, Ignacio (ZARCH, 2024)
ANGELA MILLION, CHRISTIAN HAID, IGNACIO CASTILLO ULLOA, NINA BAUR Spatial Transformations. Kaleidoscopic Perspectives on the Refiguration of Spaces Technische Universität Berlin, London, 2021, 321 pp. Tapa blanda. 38,97 € Idioma: inglés ISBN: 978-1-032-11453-8